The influence of social and commercial pension insurance differences and social capital on the mental health of older adults—Microdata from China - Chai, Kuang-Cheng; Li, Qiang; Jin, Chengsheng; Lu, Yu-Jiao; Cui, Zhenxin; He, Xingxing (Frontiers in Public Health, 2022)
Abstract: The number of older adults is rising rapidly in China. Various concerns such as chronic diseases, financial inadequacy and a feeling of loneliness have adversely affected the mental health of older adults, and this has become an important public health and social issue. To realize healthy aging, the Nineteenth National People’s Congress of China put forth the Healthy China strategy, speeding up the promotion activities of mental health and pension measures, carrying out public welfare pension insurance for the entire population, and contributing to the mental health of older adults. This study used data from China Family Panel Studies. This study mainly uses the random effect estimation method (random effect, RE) and the feasible generalized least squares estimation method (FGLS) to control for heterogeneity to explore the impact of social and commercial pension insurance on the mental health of older adults, the moderating effect of social capital on pension insurance, and the mental health of older adults. The results showed that social pension insurance is proportional to the mental health of older adults, whereas commercial pension insurance is inversely proportional to mental health. Social capital had a significant moderating effect on pension insurance. When a country develops an aging economy, the emphasis on social capital helps make targeted industrial development suggestions. The government’s expansion of insurance coverage is crucial for improving the mental health of older adults.